Beauty's punishment #2 : an erotic novel of discipline, love and surrender, for the enjoyment of men and women - Roquelaure, A. N. (Beauty, 1999)
Beauty is sold into erotic slavery and forced to obey the orders of the Captain and Mistress Lockley.